2001
DOI: 10.1029/2000jd000044
|View full text |Cite
|
Sign up to set email alerts
|

Thick ice layers in snow and frozen soil affecting gas emissions from agricultural soils during winter

Abstract: Abstract. We investigated soil and snow cover gas concentrations at two agricultural sites (St-Lambert; Chapais) in Quebec, Canada, during winter 1998-1999. Both sites showed frozen and unfrozen soils and complex snow cover structure. At St-Lambert we measured

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 34 publications
4
31
0
1
Order By: Relevance
“…The studied area has the most intensive livestock production of the watershed, which generates a surplus of nutrients. Slope of the fields in the studied area ranges from 0% to 9%, which increases the risk of surface runoff, soil water erosion, and the transport of sediments, phosphorus, and other contaminants (pathogens, herbicides, and trace elements) from agricultural land to streams [6]. Figure characteristics, were measured in 12 fields and are described in Tables 1 and 2.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The studied area has the most intensive livestock production of the watershed, which generates a surplus of nutrients. Slope of the fields in the studied area ranges from 0% to 9%, which increases the risk of surface runoff, soil water erosion, and the transport of sediments, phosphorus, and other contaminants (pathogens, herbicides, and trace elements) from agricultural land to streams [6]. Figure characteristics, were measured in 12 fields and are described in Tables 1 and 2.…”
Section: Study Areamentioning
confidence: 99%
“…Environmental conditions in spring can significantly affect water transport. Early snow accumulation on wet soils may result in more unfrozen soils [6], or shallowly frozen soils, that allow higher infiltration of water at spring melt which consequently decreases runoff [7,8]. Late snow accumulation on relatively dry soils with cold air temperatures will allow frost to penetrate deeper below the soil surface.…”
Section: Introductionmentioning
confidence: 99%
“…The static closed-chamber method has been used to evaluate CO2 emissions from farmland (e.g., van Bochove et al, 2001;Kusa et al, 2008;Shimizu et al, 2009). These reports described that the seasonal variation of CO2 flux peaked in summer with the highest soil temperature and that it was almost zero in winter with snow and soil frost.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have measured soil CO2 concentrations (e.g., van Bochove et al, 2001;Hirano et al, 2003;Chen et al, 2005;Maljanen et al, 2007;DeSutter et al, 2008;Muhr et al, 2009;Liang et al, 2010). These studies revealed seasonal variations in CO2 concentrations; the CO2 concentrations peaked in summer and had been increasing during the snow-covered period, which suggests that the stored CO2 in the soil during the winter might be released to the atmosphere after the Full Paper J.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation